Pengaruh Pelatihan dan Kepemimpinan Terhadap Kompetensi Guru MTs Negeri Selat Panjang - Marpaung, Rio; ', Surizal; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to find to determine effect training and leadership on teacher competence of MTs in Selatpanjang, either simultaneously or partially and which variables are the most powerful influence on teacher's competence of MTs in Selat panjang. The method used in this study is a descriptive statistical analysis and multiple linear regression analysis. The sample was the entire population of teachers of MTs Selatpanjang totaling 42 people with census techniques. The results of the simultaneous regression test (Test-F) showed that all independent variables consisting of leadership training and have a significant impact on teacher competence variables. Partial regression test (t-test) showed that the training variables have the most significant effect on the variables of teacher competence. The magnitude of the effect that (R²) by training and leadership together to variable competence of teachers is 78.5%, while the remaining 21.5% is influenced by other variables that are not observed in this study. Results and discussion of research and concluded that training and leadership simultaneously positive and significant impact on teacher competence MTs Selatpanjang. Demikianpula, training and leadership partially positive and significant impact on teacher competence MTs Selatpanjang. Variables that most strongly to MTs Selatpanjang teacher competence is training.Keywords : Training, Leadership and Competence